Appearance, disappearance and reappearance of activity based costing: a case study from a Sri Lankan manufacturing firm / Tharusha Gooneratne and Chamali Wijerathne - Gooneratne, Tharusha; Wijerathne, Chamali (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA (UiTM) Shah Alam, 2019)
The purpose of this paper was to identify why activity based costing (ABC) implementation in organizations at times do not continue despite their early interest, but later regain importance. Using the qualitative case study approach, the paper explored the reasons for the appearance, disappearance and reappearance of ABC drawing field data from a Sri Lankan porcelain manufacturing firms, called Gamma. Guided by the theoretical underpinnings of the Actor-Network Theory (ANT), and the translation process therein, we follow organizational managers (human actors) and their interactions with various objects and systems (non-human actors) within the particular context of Gamma, during the different phases of the ABC project. Our findings suggest that the appearance, disappearance and reappearance of ABC have been shaped by a network of actors comprising both humans and non-humans, and that the implementation and continuation of ABC is constrained by the interests of these various actors both inside and outside of the firm. While most prior research has focused on a single phase of ABC implementation, such as the success or the failure, this study brings out its reappearance, following a phase of appearance and disappearance, hence it is a useful addition to prior literature. Furthermore, the findings of this research have important implications for practitioners who are striving to revive projects, such as ABC in organizations.